Legacy effects of infection in patients with heart failure: a national cohort study of 31, 318 patients in Taiwan. (3rd October 2022) - Chen, C Y; Li, Y H; Lee, C H; Lin, H W; Lin, S H
Abstract: Background: Although infection is a common cause of hospitalization in patients (pts) with heart failure (HF), the long-term cardiovascular (CV) prognosis in HF after infection is not well studied. Methods and results: From 2009 to 2015, 310, 485 pts with their first HF admissions and survival to discharge were identified from the National Health Insurance Research Database. Among the pts, 103, 505 (33.3%) were readmitted within 1 year after HF discharge for infection, including pneumonia (44.2%), urinary tract infection (UTI) (37.9%), skin and soft tissue infections (9.7%), and others (8.1%). Those without admission for any infection were controls. We compared the primary composite endpoint, including all-cause death, acute myocardial infarction (AMI), stroke, and hospitalization for HF (HHF) between the 2 groups after the infection episode. After propensity score matching, the clinical characteristics (age 71.7±13.9 years, male 52.0%) and treatment were similar between the groups (n=15, 659 in each group). In a mean follow-up time of 4.3±2.9 years, 86.2% pts with a history of infection admission and 63.6% pts in the control group met the primary endpoint. Multivariate Cox proportional hazards analysis showed the infection group had a higher risk of the primary composite endpoint (HR 1.760, 95% CI 1.714–1.807), including all-cause death (HR 1.587, 95% CI: 1.540–1.636), HHF (HR 1.993, 95% CI 1.922–2.066), AMI (HR 1.332, 95% CI 1.224–1.450), and stroke (HR 1.769, 95% CI 1.664–1.882). In infection group, HHF was the earliest outcome event with a mean time of 17.5 months and mortality is the second early event with a mean time of 23 months after discharge from the infection episode. Pneumonia carried a higher risk than UTI for the primary composite endpoint (HR 1.140, 95% CI 1.104–1.178). Conclusions: One-third of HF pts discharged from the hospital experienced acute infection that required readmission. The pts had worse CV prognosis after readmission for infectious disease compared to those without infection Funding Acknowledgement: Type of funding sources: Private hospital(s). Main funding source(s): This study is supported by National Cheng Kung University Hospital and Tainan Hospital, Ministry of Health and Welfare, Taiwan.